2010
DOI: 10.1038/hr.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary aldosteronism among prehypertensive and stage 1 hypertensive subjects

Abstract: Recent studies have reported a high prevalence of primary aldosteronism among patients with severe hypertension. However, the prevalence of this disease among normotensive and mildly hypertensive patients has not been determined. The aim of this study was to examine the prevalence of primary aldosteronism among prehypertensive and stage 1 hypertensive subjects. A total of 292 adult subjects with hypertension or prehypertension was screened for primary aldosteronism. Subjects with a plasma aldosterone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 28 publications
0
55
0
4
Order By: Relevance
“…Primary aldosteronism (PA) is the most common form of secondary hypertension, with an estimated prevalence of 5-15% in all hypertensive patients [1,2]. Excess aldosterone has adverse cardiovascular and renal consequences in patients with hypertension and in patients with diabetes mellitus or chronic renal disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Primary aldosteronism (PA) is the most common form of secondary hypertension, with an estimated prevalence of 5-15% in all hypertensive patients [1,2]. Excess aldosterone has adverse cardiovascular and renal consequences in patients with hypertension and in patients with diabetes mellitus or chronic renal disease [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…confirmatory testing, would have confirmed positive for PA. The starting sample size of 296, however, was comparable to other primary care prevalence studies in which retention of subjects for further screening was low, and prevalence was similar to ours (13,21,22 Using a similar ARR cutoff as our study (ARR ≥ 25), they reported a 7.5% prevalence on screening. Although the prevalence in that study is similarly low to that demonstrated in our population, the U.K. study utilized a more stringent ARR cutoff for screening (ARR cutoff ≥ 40) (23).…”
Section: Discussionmentioning
confidence: 70%
“…performed in limited populations, specifically those with patients referred to subspecialty centers for the management of hypertension. Few studies have endeavored to determine the disease prevalence in the primary care setting (21)(22)(23)(24). Furthermore, screening of patients for PA in general hypertensive populations is often overlooked unless patients have concomitant hypertension and hypokalemia.…”
Section: Introductionmentioning
confidence: 99%
“…This is far more common than in people with non-resistant hypertension, 2 although a high prevalence of PA has also been reported among prehypertensive and stage 1 hypertensive Japanese patients. 3 The first step in screening for PA is measurement of the aldosterone-to-renin ratio (ARR); a combined evaluation of ARR with the serum sodium to urinary sodium divided by the serum potassium 2 to urinary potassium ratio (ARRÂSUSPPUP) seems to be the most reliable screening test, with a sensitivity of 92.3% and a specificity of 93.9%. 4 Surgery is an option in patients with unilateral adrenal disease.…”
mentioning
confidence: 99%